Memperkuat Integrasi Nasional Melalui Generasi Bangsa Dan Teknologi Pada Pembelajaran Pendidikan Kewarganegaraan - Yunita Yasmin Istiqomah; Dinie Anggraeni Dewi (Journal of Education, Humaniora and Social Sciences (JEHSS), 2021)
An integration has been going on from time immemorial until now, continuity and the occurrence of rapid development of something is truly important and has a meaning that is not only memorable but also influential to other human beings. The purpose of this paper is to find out whether there is still a sense of nationalism that is still inherent in the nation's generation. The method used is the method of collecting data from relevant journals with the title Strengthening National Integration through National Generation and Technology in Citizenship Education Learning, so that this paper produces the importance of the national spirit in the nation's generation. In today's world, technology is increasingly advanced in all corners of the world, so the importance of reminding each other to have a high fighting spirit, if this is not realized, it will cause a crisis of National integration that exists in Indonesia in the 21st century. The Age of Technology can be a medium for Indonesian society to have a strong integration in every field through Citizenship Education (PKN) lessons.